Relationship between the Characteristics of Vaginal Secretion, Reproductive Immune Antibody and Infertility: Vaginal Secretion, Reproductive Immune Antibody and Infertility - Cao, Huabin; Wang, Lu; Wu, Huanhuan (Cellular and Molecular Biology, 2022)
Infertility is still a hot topic in the field of reproductive medicine. In this paper, the detection of vaginal secretions and the positive rate of serum reproductive immune antibody in infertile women and normal pregnant women were used to explore the correlation between infertility and the two, so as to provide an effective scientific basis for the diagnosis and treatment of infertility. In this paper, 80 infertile patients (experimental group) and normal pregnant women (control group) were selected for the experiment. Real-time PCR was used to detect vaginal secretion and enzyme-linked immunosorbent assay. The results showed that the positive rates of UU and CT were 42.5% and 40%, respectively. The positive rate of the control group was 8.8% (Uu) and 7.5% (CT). In addition, the positive rates of ANA and AsAb in the experimental group were 40% and 44%, respectively, and those in the control group were 7.5% and 8.8%, respectively, with a significant difference (P<0.01). The correlation coefficients between the two antibodies and the occurrence of infertility were 0.501 (ANA) and 0.663 (AsAb), and there was a correlation (P<0.05).